Impact of Radiation Therapy on Outcomes of Artificial Urinary Sphincter: A Systematic Review and Meta-Analysis - Zhang, Li; Xu, Yanwen (Frontiers in Surgery, 2022)
Background: To compare incontinence rates and complications in patients receiving artificial urinary sphincter (AUS) with or without radiotherapy (RT). Methods: PubMed, Embase, ScienceDirect, CENTRAL, and Google Scholar databases were searched for studies comparing outcomes of AUS between patients with and without RT. Search limits were from 1st January 2002 to 15th September 2021. Results: Eighteen studies were included. Meta-analysis revealed statistically significant reduced odds of the absence of incontinence in the RT group (OR: 0.35 95% CI: 0.21, 0.59 I2=51% p<0.0001) as compared to the no-RT group. We also noted statistically significant increased risk of revision surgery in the RT group (OR: 1.74 95% CI: 1.16, 2.60 I2=73% p=0.07). There was increased risk of infections (OR: 2.51 95% CI: 1.00, 6.29 I2=46% p=0.05) and erosions (OR: 2.00 95% CI: 1.15, 3.45 I2=21% p=0.01) in the RT group, but the difference was significant only for erosions. Meta-analysis revealed a statistically significant increased risk of explantation in patients with RT (OR: 3.00 95% CI: 1.16, 7.75 I2=68% p=0.02) but there was no difference in the risk of urethral atrophy (OR: 1.18 95% CI: 0.47, 2.94 I2=46% p=0.72) and mechanical failure (OR: 0.90 95% CI: 0.25, 3.27 I2=54% p=0.87) between the two groups. Conclusions: Our meta-analysis of recent studies indicates that RT significantly reduces the odds of achieving complete continence after AUS placement. History of RT does not increase the risk urethral atrophy or mechanical failure in patients with AUS. However, the risk of revision surgery, erosions and explantations is significantly increased in patients with RT with a non-significant but increased tendency of infections.